Effects of Sophora japonica flowers (Huaihua) on cerebral infarction - Hsieh Ching-Liang; Chen Hsiang-Ni (Chinese Medicine, 2010)
Abstract The dried flowers and buds of Sophora japonica are used as a medicinal herb in China, Japan and Korea to treat bleeding hemorrhoids and hematemesis. This article presents an overview of the effects of Sophora japonica on cerebral infarction based on literature searched from Medline, PubMed, Cochrane Library and the China National Knowledge Infrastructure (CNKI). Sophora japonica contains both anti-hemorrhagic and anti-hemostatic substances. Sophora japonica reduces cerebral infarction partly as a result of its anti-oxidative and anti-inflammatory activities. Previous studies found that Sophora japonica reduced the size of cerebral infarction and neurological deficits and reduced microglial activation, interleukin-1β release and number of apoptotic cells in ischemia-reperfusion injured Sprague-Dawley rats. Further study is required to determine the relationship between Sophora japonica-mediated reduction in cerebral infarction size and the effects of Sophora japonica on platelet aggregation and cardiovascular function.